2019
DOI: 10.22260/isarc2019/0023
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Bridge Conditions in Ontario: A Case Study

Abstract: Maintenance and repair of bridges represent significant costs in provincial and municipal government budgets. Prediction of bridge conditions can help managers in annual cost estimating and budget allocation. To assess Bridge Condition Index (BCI), each bridge component must be inspected every two years, tested if it is required, and rated. Bridge condition can be affected over time by different attributes such as material, structure, location, and use. This paper presents a study conducted to model and predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Firstly, they have been successful in data-driven structural health-monitoring [63][64][65][66][67] and investigating infrastructure problems in previous studies [28,33,68,69]. Secondly, the existing studies have demonstrated the effectiveness of Random Forest [70,71], XGboost [22,28], and ANN [25,29,33,72,73] in capturing the complex and nonlinear relationships among the variables involved in predicting bridge condition rating. The following is a general overview of the models trained and evaluated in this study.…”
Section: Results Of Training and Evaluating Modelsmentioning
confidence: 99%
“…Firstly, they have been successful in data-driven structural health-monitoring [63][64][65][66][67] and investigating infrastructure problems in previous studies [28,33,68,69]. Secondly, the existing studies have demonstrated the effectiveness of Random Forest [70,71], XGboost [22,28], and ANN [25,29,33,72,73] in capturing the complex and nonlinear relationships among the variables involved in predicting bridge condition rating. The following is a general overview of the models trained and evaluated in this study.…”
Section: Results Of Training and Evaluating Modelsmentioning
confidence: 99%
“…In particular, the existing method underestimates the occurrence probabilities of DC 2 and DC 3 in the latter part of the bridge life (after approximately 20 years of bridge age), which can be attributed to the fact that the deterioration process estimated by the existing method is not time dependent. In Taghaddos and Mohamed (2019), a condition with a BCI value of 70 or less is defined as a condition requiring maintenance. In this study, although it is a slightly pessimistic assessment, it is supposed that DC 3, which has a BCI of 75 or less as shown in Table 3, is a condition that requires maintenance.…”
Section: Comparison With Homogeneous Ctmcmentioning
confidence: 99%
“…In such processes, it cannot be denied that predicting deterioration for each bridge element may result in an overly detailed analysis. In addition, it is suggested that prediction of entire bridge deterioration is still meaningful because (1) BCI is still being recorded in the Ontario data set used in this study and (ii) analyses that predicted deterioration by BCI for entire bridges have been actively conducted in recent years (Taghaddos & Mohamed, 2019). For these reasons, the authors decided to use the BCI for the entire bridge as a deterioration index in this real‐world example, while also recognizing the importance of predicting deterioration for each bridge element.…”
Section: Real‐world Examplementioning
confidence: 99%